OPTIMASI PEMAKAIAN JAM KERJA DAN BAHAN BAKU DALAM MEMPRODUKSI MINUMAN INSTAN TRADISIONAL - Sondang Kiki Rosita; Totok Herwanto; Ahmad Thoriq; Boy Macklin Pareira (AGROINTEK, 2019)
CV. Cihanjuang Inti Teknik is a small or medium-sized business (UKM) engaged in the traditional beverage processing industry. The company is faced with problems of use to optimize the use of work time so that there is no idle work time or overtime working hours. Other problems, so far the procurement of raw materials carried out is also only based on estimates, namely with raw materials made in stock without taking into account quantitative calculations. The goal programming method is used with the aim of analyzing and describing the optimal use of resources in working hours and raw materials from the average production target needed by the company. The calculation of goal programming is supported by using LINDO (Linear Interactive Discrete Optimizer) program to obtain the optimal number of products from working hours and raw materials needed by the company. The results of the study obtained optimal regular working hours in scenarios I, II, III, and IV respectively in the amount of 159.95 hours/month, 174.25 hours/month, 176.26 hours/month and 192.37 hours/month. There was also an increase in the use of raw materials for ginger, coffee, ginseng and pepper in scenario II, raw materials for ginger, white and vanilla sugar in scenario III, raw materials for white sugar, vanilla and cinnamon in scenario IV.